Early parent-child interactions and substance use disorder: An attachment perspective on a biopsychosocial entanglement. (December 2021) - Gerra, Maria Lidia; Gerra, Maria Carla; Tadonio, Leonardo; Pellegrini, Pietro; Marchesi, Carlo; Mattfeld, Elizabeth; Gerra, Gilberto; Ossola, Paolo
Highlights: Substance use disorders vulnerability is rooted in neurobiological developmental pathways. Insecure attachment and trauma are greater risk factors for developing substance use disorders. Vulnerability to substance use disorders involve genetic, epigenetic and neuroendocrine changes. Parenting represents a therapeutic target for prevention of addiction. Abstract: This review aims to elucidate environmental and genetic factors, as well as their epigenetic and neuroendocrine moderators, that may underlie the association between early childhood experiences and Substance Use Disorders (SUD), through the lens of parental attachment. Here we review those attachment-related studies that examined the monoaminergic systems, the hypothalamic pituitary adrenal stress response system, the oxytoninergic system, and the endogenous opioid system from a genetic, epigenetic, and neuroendocrine perspective. Overall, the selected studies point to a moderating effect of insecure attachment between genetic vulnerability and SUD, reasonably through epigenetic modifications. Preliminary evidence suggests that vulnerability to SUDs is related with hypo-methylation (e.g. hyper-expression) of high-risk polymorphisms on the monoaminergic and hypothalamic pituitary adrenal system and hyper-methylation (e.g. hypo-expressions) of protective polymorphisms on the opioid and oxytocin system. These epigenetic modifications may induce a cascade of neuroendocrine changes contributing to the subclinical and behavioural manifestations that precede the clinical onset of SUD. Protective and supportive parenting could hence represent a key therapeutic target to prevent addiction and moderate insecure attachment.